Script concordance test to train clinical reasoning in speech therapy students - del Campo Rivas, Manuel Nibaldo; Silva-Ríos, Angélica Pilar (Revista de Investigación en Logopedia, 2023)
The script concordance test has been used in the training and evaluation of clinical reasoning (CR) as an innovative strategy in higher education. However, there is no evidence of its application in undergraduate speech therapy students. The aim of this research was to analyze the performance and perception of speech therapy students regarding the use of scripts. A pre-experimental and multicenter pilot was designed, complemented with three focus groups. Quantitative variables were summarized through means and standard deviation (SD). The comparison between groups was performed with Anova one way and Bonferroni post hoc test, with a significance level of p
Keywords: Speech-language therapy; Pedagogical innovation; Reasoning; Higher education